THE EFFECTS OF CELEBRITY ENDORSEMENT ON BRAND REPUTATION AND CONSUMER BEHAVIOUR AMONG MALAYSIAN UNIVERSITY STUDENTS - Foo Ni En, Nicolette; Yong, Xin Yi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates the effectiveness of celebrity endorsements as a marketing strategy, with particular attention to its impact on brand reputation and consumer behavior among university students. Method: Guided by social identity theory, a quantitative survey was administered to 104 university students to examine the extent to which celebrity endorsements influence purchasing decisions. Results: The findings reveal that celebrity endorsements significantly affect brand perception and consumer behavior, driven largely by societal pressures and the aspirational appeal of celebrities. While social identity factors heighten susceptibility to celebrity influence, rational considerations such as price, quality, and personal preference continue to play a decisive role in consumer choices. Novelty: This study contributes to the existing literature by integrating social identity theory to elucidate the dual forces of social belonging and rational evaluation in shaping consumer responses to celebrity endorsements, offering a more nuanced understanding of the psychological mechanisms underlying marketing effectiveness.